Fractionation and Partial Characterization of the Products of Autolysis of Cell Walls of Bacillus subtilis - Young, Frank E. (1966)
Young, Frank E. (Western Reserve University, Cleveland, Ohio). Fractionation and partial characterization of the products of autolysis of cell walls of Bacillus subtilis. J. Bacteriol. 92:839–846. 1966.—Autolysis of the cell wall of Bacillus subtilis by an indigenous autolytic enzyme results in solubilization of 90% of the cell wall. The solubilized cell wall (supernatant fraction) was fractionated by the combination of ion-exchange chromatography on diethylaminoethyl cellulose and gel filtration on Sephadex G-25 into polysaccharides (composed of N-acyl glucosamine and N-acyl muramic acid), mucopeptides, peptides, and teichoic acid. The chemical composition of the products of autolysis confirms the proposed mechanism of autolysis and establishes the autolytic enzyme as an N-acyl muramyl-l-alanine amidase. The heteropolymers in the cell wall are linked by peptide bridges. Two peptides which account for 70% of the peptides of the cell wall have a molar ratio of 1.0:0.9:1.3 for diaminopimelic acid, glutamic acid, and alanine, respectively. Other minor peptides contain diaminopimelic acid, glutamic acid, and alanine in molar ratios of 1.0:0.9:1.5, 1.0:0.5:1.0, and 1.0:1.5:1.7, respectively. The procedures employed in this study should be applicable to the fractionation of heteropolymers in cell walls of other gram-positive organisms and thereby aid in the study of the structure of antigenic determinants and endotoxins.